FAKTOR-FAKTOR YANG MEMPENGARUHI ANTI-CORUPTION DISCLOSURE - Nadia Agustina; Anitaria Siregar (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2025)
This study aims to analyze the influence of an independent commissioner, independent audit committee, audit quality, and institutional ownership on anticorruption disclosure. This research uses a purposive sampling method with 53 companies as the sample. The sample is the energy company listed in Indonesia Stock Excange from 2021 to 2023. The data analysis methods used are multiple linear regression. Statistical for social science software version 30 is used for testing. The results of the hypothesis test show that independent commissioner, audit quality, and institutional ownership positively influence anticorruption disclosure. Meanwhile, independent audit committees negatively influence anticorruption disclosure. This research shows that the importance of good corporate governance can increase the transparency and accountability of the company energy sector.